2015
DOI: 10.1155/2015/752424
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Mesenchymal Stem Cell Behavior Using Human Hair Keratin-Coated Surfaces

Abstract: Human mesenchymal stem cells (hMSCs) have shown great potential for therapeutic purposes. However, the low frequencies of hMSCs in the body and difficulties in expanding their numbers in vitro have limited their clinical use. In order to develop an alternative strategy for the expansion of hMSCs in vitro, we coated tissue culture polystyrene with keratins extracted from human hair and studied the behavior of cells from 2 donors on these surfaces. The coating resulted in a homogeneous distribution of nanosized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 33 publications
5
19
0
1
Order By: Relevance
“…Similar fibroblastic appearance of pASCs was also found by other groups . Recently, Hartrianti et al compared the behaviors of human MSCs on keratin coating plates and TCPS . They also found that keratin improved hMSC proliferation and even enhanced STRO‐1 expression.…”
Section: Discussionsupporting
confidence: 70%
“…Similar fibroblastic appearance of pASCs was also found by other groups . Recently, Hartrianti et al compared the behaviors of human MSCs on keratin coating plates and TCPS . They also found that keratin improved hMSC proliferation and even enhanced STRO‐1 expression.…”
Section: Discussionsupporting
confidence: 70%
“…20 Hair keratin coatings, in particular, could bring about new breakthroughs as bioactive interfaces on cell culture substrates, having been shown to encourage ECM production 9 and to moderate donor-to-donor variability while maintaining stem cell proliferative capacities. 10 In the current study, keratin was successfully coated on silica beads, which are advantageous as a cell culture substrate themselves. Silica beads are chemically inert and extremely stable; they provide a FIGURE 5.…”
Section: Discussionmentioning
confidence: 99%
“…9 Similarly, coated surfaces could also enhance the colony forming efficiency of mesenchymal stem cells and maintain their pluripotency over serial passages. 10 These studies have strengthened our understanding that human hair keratin has the potential to modulate cell behavior.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Film formed have good mechanical properties due to large amount of cystine linkage. Recently, human hair keratin was used for keratin-based biomaterials, which have been utilized for tissue regeneration ( Lee 2014) and humanhair keratin to enrich human mesenchymal stem cells for clinical applications (Hartrianti et al 2015).…”
Section: Keratins In Biomedical Applicationsmentioning
confidence: 99%